2015
DOI: 10.1080/15389588.2015.1051222
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting the severity of traffic accidents at Shanghai river-crossing tunnel

Abstract: This article aims to provide useful information for engineers to develop interventions and countermeasures to improve tunnel safety in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
5
18
0
Order By: Relevance
“…This finding supports previous literature reports, where the main factor affecting traffic injury severity was determined to be the designed road geometry [60,61] and one of the factors that was significantly related to severity was road wetness [62,63]. In addition, it has been found that the traffic accident severity correlates with Dg and that male drivers show increased severity [64].…”
Section: Discussionsupporting
confidence: 90%
“…This finding supports previous literature reports, where the main factor affecting traffic injury severity was determined to be the designed road geometry [60,61] and one of the factors that was significantly related to severity was road wetness [62,63]. In addition, it has been found that the traffic accident severity correlates with Dg and that male drivers show increased severity [64].…”
Section: Discussionsupporting
confidence: 90%
“…There was a significant difference in terms of fatality of RTIs between elderly and non-elderly people. Several studies, all around the world, have confirmed the subject [ 23 , 70 - 73 ]. The main reason is the physical conditions of elderly people as their physical power is atrophied and mitigated and makes them more vulnerable when they face RTIs.…”
Section: Discussionmentioning
confidence: 94%
“…Yeung and Wong [12] studied the characteristics of 608 traffic accidents occurred in expressway tunnels in Singapore during 2009-2011, and accorded to the location of traffic accidents, the location of tunnels is classified. Lu et al [13] described the temporal and space distribution characteristics of traffic accidents occurred in river-crossing tunnels of Shanghai. Ma et al [14] and Zhang et al [15] explored the major distribution characteristics and rules of TTAs based on the statistical analyses of TTAs of the Shaoguan section of the Beijing-Zhuhai expressway, the causes of traffic accidents were determined, and the practical countermeasures were proposed.…”
Section: Introductionmentioning
confidence: 99%